أهمية وجود لجان المراجعة في المؤسسات الإقتصادية الجزائرية ودورها في تعزيز جودة آداء المراجع الخارجي والحد من الفساد المالي - بوقفة، علاء (My University, 2024)
This study aims to identify the importance of the existence of audit committees in Algerian economic institutions and their role in enhancing the professional performance quality of external auditors and reducing financial corruption. To achieve the study's objectives and test its hypotheses, opinions were surveyed from a sample of accountants, audit supervisors, accounting experts, and specialized professors in Algeria through the distribution of a questionnaire. The collected data were subjected to statistical analysis using the SPSS statistical package. The results of the study showed a consensus among the surveyed sample on the urgent need to establish and adopt audit committees in Algerian economic institutions. The study also found that audit committees play an effective role in enhancing the quality of external auditors' performance, as well as significantly contributing to reducing financial corruption by monitoring the risks associated with the institution's performance
The importance of audit committees in Algerian economic institutions and their role in enhancing the quality of external auditor performance and reducing financial corruption.
Keywords: لجان مراجعة; مراجع خارجي; فساد مالي; تقارير مالية; Audit Committees; External Auditor; Financial Corruption; Financial Reports